Characteristics of Knowledge of Pregnant Women About Pregnancy Exercises in the Working Area of Sungai Bilu Health Center Banjarmasin - ari lestari, nur cahyani; Diaty, Rima; Fathiyati, Fathiyati (LPPM AKPER FATMAWATI, 2022)
The purpose of this study was to determine the characteristics of pregnant women's knowledge about pregnancy exercise in the working area of Sungai Bilu Public Health Center. This study used a descriptive method with a population of all third trimester pregnant women who came to the Sungai Bilu Health Center from January to May. While the sampling technique in this study used the accidental sampling technique, namely all third trimester pregnant women who visited Sungai Bilu Health Center with a total of 30 respondents. The results of this study were that most of the respondents did not participate in pregnancy exercise activities, namely from 30 respondents who actively participated in pregnancy exercise activities as many as 10 people (30%) and who were not active as many as 20 people (70%) where respondents who had less knowledge were 11 people (36 ,7%), respondents who have sufficient knowledge are 14 people (46.7%) and respondents who have good knowledge are 5 people (16.6%). The conclusion of this study was that most of the respondents did not participate in pregnancy exercise because they did not know about the benefits and objectives of pregnancy exercise.